2023
DOI: 10.1002/smll.202205739
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Delivery Shippers for Noncoding RNA‐Based Modulation of Angiogenesis: Insights from Ischemic Stroke and Cancer

Abstract: Ischemic stroke and systemic cancer are two of the leading causes of mortality. Hypoxia is a central pathophysiological component in ischemic stroke and cancer, representing a joint medical function. This function includes angiogenesis regulation. Vascular remodeling coupled with axonal outgrowth following cerebral ischemia is critical in improving poststroke neurological functional recovery. Antiangiogenic strategies can inhibit cancer vascularization and play a vital role in impeding cancer growth, invasion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 319 publications
0
3
0
Order By: Relevance
“…Cancer-related exosomes, released by cancer cells and other cells in the tumor micro-environment, play regulatory roles in the progression, migration, and deterioration of multiple cancers ( Sandua et al, 2021 ). CircRNAs can be a novel type of therapeutic targets, by functioning as tumor suppressors or oncogenes ( He et al, 2021 ; Pan et al, 2023 ). Accumulated studies have revealed that cancer cells could release circRNAs to the surrounding recipient cells via exosome-mediated transport strategies, thus affecting the carcinogenesis and therapeutic response ( Liu et al, 2021b ; Fontemaggi et al, 2021 ; Zhang et al, 2023 ).…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Cancer-related exosomes, released by cancer cells and other cells in the tumor micro-environment, play regulatory roles in the progression, migration, and deterioration of multiple cancers ( Sandua et al, 2021 ). CircRNAs can be a novel type of therapeutic targets, by functioning as tumor suppressors or oncogenes ( He et al, 2021 ; Pan et al, 2023 ). Accumulated studies have revealed that cancer cells could release circRNAs to the surrounding recipient cells via exosome-mediated transport strategies, thus affecting the carcinogenesis and therapeutic response ( Liu et al, 2021b ; Fontemaggi et al, 2021 ; Zhang et al, 2023 ).…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), which are encapsulated in EVs, are involved in AS and VC [ 76 , 77 ]. ncRNAs shuttled via EVs may control post-hypoxia tissue survival and remodeling by regulating cell injury and inflammatory responses in MI and stroke [ 78 , 79 ]. Cardiomyocytes increase the secretion of EVs during stress, such as hypoxia, inflammation, or injury [ 80 ].…”
Section: Evs In Atherosclerosis and Cardiovascular Diseasesmentioning
confidence: 99%
“…LncRNA enrichment in EVs has been extensively studied in various contexts, including tumors (Geng et al, 2023; Wu et al, 2023), cardiovascular diseases (Jiapaer et al, 2023), diabetes mellitus (Gauthier et al, 2022), ischemic stroke (Pan et al, 2023), and Alzheimer's (Canseco‐Rodriguez et al, 2022), among others. However, studies that concentrate on exosomal lncRNAs in parasitology are few.…”
Section: Lncrnas In Malariamentioning
confidence: 99%